A Case study on the Movie and Television Review and Classification Board in relation to Presidential Decree 1986 - Antiojo, Jenny Lyn M. 1979-
This study dealt with how the MTRCB functions as an organisation. This study performed an analysis of the implementing rules and regulations of the MTRCB. PD 1986 was discussed thoroughly in the study. A connection between PD 1986 and the MTRCB's rules and regulations was established. The study showed the extent to which PD 1986 was considered in creating the implementing rules and regulations which the MTRCB uses in its daily operation. This study proves that the MTRCB has deviated from the prescriptions of PD 1986. It also proves the inadequacy of PD 1986 as basis for the current operation of the MTRCB.